A method for determining the La content in tungsten alloy
Through inductively coupled plasma atomic emission spectrometer combined with high-temperature oxidation and chemical dissolution steps, the problem of sample pretreatment pollution in the determination of La element content in tungsten alloy is solved, and efficient and accurate La element content determination is achieved to meet the quality control needs of tungsten alloys .
Patent Information
- Application Number
- CN202411470682.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The method for measuring the La element content in tungsten alloys in the prior art has problems of contamination during sample pretreatment, and the operation is complicated and the detection period is long, making it difficult to meet the needs of tungsten alloy quality control.
The inductively coupled plasma atomic emission spectrometer was used to determine the lanthanum element. By oxidizing the sample at high temperature, dissolving hydrogen peroxide, precipitating magnesium salt in triethanolamine solution, dissolving nitric acid and perchloric acid, eliminating background and spectral line interference, improving the accuracy of measurement .
It realizes rapid and accurate determination of La element content in tungsten alloy, reduces the pollution of sample pretreatment, simple operation, few interferences, and low detection limit, and meets the measurement requirements of the rare earth element La in tungsten alloy.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of tungsten alloy detection, and in particular relates to a method for determining the La element content in a tungsten alloy. Background Art
[0002] Tungsten has the characteristics of high hardness, high melting point, no air erosion at room temperature, and relatively stable chemical properties. It is widely used in cemented carbide, filaments, high-speed cutting alloy steel, superhard molds, optical instruments, battery manufacturing and other fields. However, pure tungsten has low-temperature brittleness, especially when tungsten materials are prepared into filaments, there are defects such as insufficient strength, easy deformation, and no pressure resistance. Studies have shown that adding rare earth La can help improve the performance of the material. The detection of the rare earth element La content is crucial for the quality control of tungsten alloys. Conventionally, spectrophotometry is used to determine the La element in tungsten alloys. This method is a traditional chemical test that requires a large amount of chemical reagents, complex steps, unstable color development, and a long detection cycle. Therefore, it is necessary to develop an accurate and rapid method for determining the La content in tungsten alloys. Summary of the invention
[0003] In order to solve the problems existing in the prior art, the main purpose of the present invention is to propose a method for determining the La content in tungsten alloy, which can reduce the pollution caused by sample pretreatment, has the advantages of simple operation, less interference, high precision, low detection limit, etc., and can well meet the determination requirements of the rare earth element La in tungsten alloy.
[0004] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:
[0005] A method for determining the La content in tungsten alloy comprises the following steps:
[0006] S1. Oxidizing the tungsten alloy sample to be tested to obtain oxide powder;
[0007] S2. The oxide powder is transferred into a beaker, and hydrogen peroxide is added and then placed in a water bath for dissolution. After the yellow solid disappears, the solution is taken out from the water bath to obtain a solution, and then ammonia water is added after cooling to room temperature to prepare a clear solution;
[0008] S3, adding triethanolamine solution to the clarified solution, precipitating lanthanum with magnesium salt as a carrier, filtering and separating with filter paper, and discarding the filtrate;
[0009] S4. Place the precipitate together with the filter paper in the original beaker, add a mixed solution of nitric acid and perchloric acid, place on a heating plate and heat to dissolve, to prepare a sample solution to be tested;
[0010] S5. Use an inductively coupled plasma atomic emission spectrometer to draw a tungsten alloy calibration curve, and measure the La intensity of the sample solution to be tested. The La content is obtained through the calibration curve to achieve the determination of the La element content in the tungsten alloy.
[0011] As a preferred embodiment of the method for determining the La content in a tungsten alloy described in the present invention, in step S1, the tungsten alloy sample to be tested is oxidized by passing compressed air into a muffle furnace, the oxidation temperature is 750-850°C, the oxidation time is 1-6h, and the compressed air flow rate is 1.5-3L / min.
[0012] As a preferred embodiment of the method for determining the La content in a tungsten alloy described in the present invention, in step S1, a sample is taken out every 1 to 2 hours during the oxidation process, placed in a dryer for cooling, the surface of the sample is cleaned, the oxide is separated from the tungsten alloy sample, and then the tungsten alloy sample is placed in a muffle furnace for oxidation, and the operation is repeated until the tungsten alloy sample is completely oxidized.
[0013] As a preferred embodiment of the method for determining the La content in tungsten alloy described in the present invention, in step S2, the water bath temperature is 60-80°C.
[0014] As a preferred embodiment of the method for determining the La content in tungsten alloy described in the present invention, in step S2, the solid-liquid ratio of oxide powder to hydrogen peroxide is (0.10-0.20) g: (10-30) mL.
[0015] As a preferred embodiment of the method for determining the La content in tungsten alloy described in the present invention, in step S2, the concentration of ammonia water is 25-28wt%, and the volume ratio of ammonia water to the dissolving solution is (1-3): (15-30).
[0016] As a preferred embodiment of the method for determining the La content in tungsten alloy described in the present invention, in step S3, the concentration of the triethanolamine solution is 1-5wt%, and the volume ratio of the clear solution to the triethanolamine solution is (1-30): (1-6).
[0017] As a preferred embodiment of the method for determining the La content in tungsten alloy described in the present invention, in step S3, the magnesium salt is added in the form of a solution, the concentration of the magnesium salt solution is 1-5wt%, and the volume ratio of the clear solution to the magnesium salt solution is (1-30): (1-3).
[0018] As a preferred embodiment of the method for determining the La content in tungsten alloy described in the present invention, in step S4, the dissolution temperature is 100-150°C.
[0019] As a preferred embodiment of the method for determining the La element content in tungsten alloy described in the present invention, wherein: in the step S4, the volume ratio of nitric acid to perchloric acid in the mixed solution of nitric acid and perchloric acid is (1-10): (1-3), and the concentration of the mixed solution of nitric acid and perchloric acid is 30-50wt%.
[0020] The beneficial effects of the present invention are as follows:
[0021] The present invention provides a method for determining the La element content in a tungsten alloy, which uses an inductively coupled plasma atomic emission spectrometer to determine the lanthanum element, and has the advantages of high precision, simple operation, less interference, and low detection limit. The present invention can avoid the contamination caused by sample pretreatment by subjecting the sample to be tested to high temperature oxidation, dissolving the oxidized sample with hydrogen peroxide, precipitating lanthanum with magnesium as a carrier in an alkaline medium of triethanolamine solution, filtering and separating to effectively remove the tungsten matrix, dissolving the precipitate with nitric acid and perchloric acid, and directly exciting with an argon plasma light source in a dilute nitric acid medium, thereby achieving the purpose of eliminating background and spectral line interference, improving accuracy, and being able to well meet the determination requirements of the rare earth element La in tungsten alloys. DETAILED DESCRIPTION
[0022] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] According to one aspect of the present invention, the present invention provides the following technical solution:
[0024] A method for determining the La content in tungsten alloy comprises the following steps:
[0025] S1. Oxidizing the tungsten alloy sample to be tested to obtain oxide powder;
[0026] S2. The oxide powder is transferred into a beaker, and hydrogen peroxide is added and then placed in a water bath for dissolution. After the yellow solid disappears, the solution is taken out from the water bath to obtain a solution, and then ammonia water is added after cooling to room temperature to prepare a clear solution;
[0027] S3, adding triethanolamine solution to the clarified solution, precipitating lanthanum with magnesium salt as a carrier, filtering and separating with filter paper, and discarding the filtrate;
[0028] S4. Place the precipitate together with the filter paper in the original beaker, add a mixed solution of nitric acid and perchloric acid, place on a heating plate and heat to dissolve, to prepare a sample solution to be tested;
[0029] S5. Use an inductively coupled plasma atomic emission spectrometer to draw a tungsten alloy calibration curve, and measure the La intensity of the sample solution to be tested. The La content is obtained through the calibration curve to achieve the determination of the La element content in the tungsten alloy.
[0030] Preferably, in step S1, compressed air is introduced into the tungsten alloy sample to be tested in a muffle furnace for oxidation, the oxidation temperature is 750-850° C., the oxidation time is 1-6 hours, and the compressed air flow rate is 1.5-3 L / min.
[0031] Preferably, in step S1, during the oxidation process, the sample is taken out every 1 to 2 hours, placed in a dryer for cooling, the surface of the sample is cleaned, the oxide is separated from the tungsten alloy sample, and then the tungsten alloy sample is placed in a muffle furnace for oxidation, and the operation is repeated until the tungsten alloy sample is completely oxidized.
[0032] Preferably, in step S2, the water bath temperature is 60-80°C.
[0033] Preferably, in step S2, the solid-liquid ratio of oxide powder to hydrogen peroxide is (0.10-0.20) g: (10-30) mL.
[0034] Preferably, in step S2, the concentration of the ammonia water is 25-28 wt %, and the volume ratio of the ammonia water to the dissolving liquid is (1-3): (15-30).
[0035] Preferably, in step S3, the concentration of the triethanolamine solution is 1-5 wt %, and the volume ratio of the clear solution to the triethanolamine solution is (1-30):(1-6).
[0036] Preferably, in step S3, the magnesium salt is added in the form of a solution, the concentration of the magnesium salt solution is 1 to 5 wt %, and the volume ratio of the clear solution to the magnesium salt solution is (1 to 30): (1 to 3).
[0037] Preferably, in step S3, lanthanum is precipitated using magnesium salt as a carrier by heating at 60-100° C. for 2-5 min and then cooling.
[0038] Preferably, in step S4, the dissolution temperature is 100-150°C.
[0039] Preferably, in step S4, the volume ratio of nitric acid to perchloric acid in the mixed solution of nitric acid and perchloric acid is (1-10):(1-3), and the concentration of the mixed solution of nitric acid and perchloric acid is 30-50wt%.
[0040] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0041] Example 1
[0042] The tungsten alloy sample to be tested is placed in a muffle furnace and oxidized at 850°C for 4 hours with compressed air, wherein the flow rate of the compressed air is 1.5 L / min, and the tungsten alloy sample is taken out every 1 hour and placed in a dryer for cooling, the surface of the tungsten alloy sample is cleaned, the oxide is separated from the tungsten alloy sample, and then the tungsten alloy sample is placed in a muffle furnace for oxidation, and the operation is repeated until the sample is completely oxidized.
[0043] Weigh 0.15 g of oxide powder and place it in a beaker, moisten it with water, add 15 mL of hydrogen peroxide, and place it in a water bath at 80° C. to dissolve to obtain a solution, and after cooling to room temperature, add 1 mL of 25 wt% ammonia water to prepare a clear solution;
[0044] Add 6 mL of 5 wt% triethanolamine solution and 2 mL of 5 wt% magnesium chloride solution, shake well, heat at 70°C for 5 min, cool; filter with medium-speed filter paper, wash the beaker 3 times and the precipitate 5 times with 2 wt% ammonia water, wash the precipitate 5 times with water, and discard the filtrate;
[0045] Place the precipitate together with the filter paper in the original beaker, add 15mL of a mixed solution of nitric acid and perchloric acid, wherein the volume ratio of nitric acid to perchloric acid is 3:1, and the concentration of the mixed solution of nitric acid and perchloric acid is 40wt%, cover with a watch glass, heat at 100℃ until thick perchloric acid smoke is emitted, until it is almost dry, remove and cool slightly, add 3mL of nitric acid, blow the watch glass and the wall of the cup with water, boil to dissolve the soluble salts, cool, transfer to a 100mL volumetric flask, dilute to the scale with water, obtain the sample solution to be tested, and perform a blank test together with the sample;
[0046] Drawing of standard working curve: Pipette 0.00mL, 0.50mL, 1.0mL, 2.0mL, 5.0mL, 10.0mL of lanthanum standard solution (100μg / mL) into a 100mL volumetric flask, add 5mL of nitric acid, dilute to scale with water, and mix well. Introduce the series of standard solutions into the inductively coupled plasma atomic emission spectrometer, measure the intensity of lanthanum in the series of standard solutions at the selected wavelength, and draw the calibration curve with mass concentration as the horizontal axis and intensity as the vertical axis.
[0047] The strength of the sample solution was tested and the lanthanum content was found on the calibration curve. The test results are shown in Table 1.
[0048] Table 1
[0049]
[0050] Comparative Example 1
[0051] The tungsten alloy sample to be tested is placed in a muffle furnace and oxidized at 850°C for 4 hours. The compressed air flow rate is 1.5L / min, and the compressed air is taken out every 1 hour and placed in a dryer for cooling. The surface of the tungsten alloy sample is cleaned, the oxide is separated from the tungsten alloy sample, and then the tungsten alloy sample is placed in a muffle furnace for oxidation. The operation is repeated until the sample is completely oxidized.
[0052] Weigh 0.15 g of oxide powder and place it in a beaker, moisten it with water, add 12 mL of hydrogen peroxide, and place it in a 70°C water bath to dissolve to obtain a solution. After cooling to room temperature, add 1 mL of 25 wt% ammonia water to make the solution clear, and cool it;
[0053] Add 4 mL of 5 wt% triethanolamine solution and 1 mL of 5 wt% magnesium chloride solution, shake well, heat at 80°C for 4 min, and cool; filter with medium-speed filter paper, wash the beaker 3 times and the precipitate 5 times with 2 wt% ammonia water, wash the precipitate 5 times with water, and discard the filtrate;
[0054] Place the precipitate together with the filter paper in the original beaker, add 10mL of a mixed solution of nitric acid and perchloric acid, the volume ratio of nitric acid to perchloric acid is 4:1, and the concentration of the mixed solution of nitric acid and perchloric acid is 40wt%, cover with a watch glass, heat at 100℃ until thick perchloric acid smoke is emitted, until it is almost dry, remove and cool slightly, add 3mL of nitric acid, blow the watch glass and the wall of the cup with water, boil to dissolve the soluble salts, cool, transfer to a 100mL volumetric flask, dilute to the scale with water, obtain the sample solution to be tested, and perform a blank test together with the sample;
[0055] Drawing of standard working curve: Pipette 0.00mL, 0.50mL, 1.0mL, 2.0mL, 5.0mL, 10.0mL of lanthanum standard solution (100μg / mL) into a 100mL volumetric flask, add 5mL of nitric acid, dilute to scale with water, and mix well. Introduce the series of standard solutions into the inductively coupled plasma atomic emission spectrometer, measure the intensity of lanthanum in the series of standard solutions at the selected wavelength, and draw the calibration curve with mass concentration as the horizontal axis and intensity as the vertical axis.
[0056] The strength of the sample solution was tested and the lanthanum content was found on the calibration curve. The test results are shown in Table 2.
[0057] Table 2
[0058]
[0059] The lanthanum in the tungsten alloy sample of Comparative Example 1 was not completely converted into lanthanum hydroxide precipitate, resulting in low accuracy of the test result.
[0060] Comparative Example 2
[0061] The tungsten alloy sample to be tested is placed in a muffle furnace and oxidized at 800°C for 3 hours. The compressed air flow rate is 2.0L / min, and the compressed air is taken out every 1 hour and placed in a dryer for cooling. The surface of the tungsten alloy sample is cleaned, the oxide is separated from the tungsten alloy sample, and then the tungsten alloy sample is placed in a muffle furnace for oxidation. The operation is repeated until the sample is completely oxidized.
[0062] Weigh 0.15 g of oxide powder and place it in a beaker, moisten it with water, add 15 mL of hydrogen peroxide to dissolve the oxide powder at 70°C to obtain a solution, then add 20 mL of ammonia water and keep it in a water bath at 80°C for 15 min, then cool it;
[0063] Filter with medium-speed filter paper, wash the beaker 3 times and the precipitate 5 times with 2wt% ammonia water, wash the precipitate 5 times with water, and discard the filtrate;
[0064] Place the precipitate together with the filter paper in the original beaker, add 15mL of nitric acid and perchloric acid mixed solution, the volume ratio of nitric acid to perchloric acid is 3:1, cover with a watch glass, heat at 120℃ until thick perchloric acid smoke is emitted, until it is almost dry, remove and cool slightly, add 3mL of nitric acid, blow water on the watch glass and the wall of the cup, boil to dissolve the soluble salts, cool, transfer to a 100mL volumetric flask, dilute to the scale with water to obtain the sample solution to be tested, and perform a blank test together with the sample;
[0065] Drawing of standard working curve: Pipette 0.00mL, 0.50mL, 1.0mL, 2.0mL, 5.0mL, 10.0mL of lanthanum standard solution (100μg / mL) into a 100mL volumetric flask, add 5mL of nitric acid, dilute to scale with water, and mix well. Introduce the series of standard solutions into the inductively coupled plasma atomic emission spectrometer, measure the intensity of lanthanum in the series of standard solutions at the selected wavelength, and draw the calibration curve with mass concentration as the horizontal axis and intensity as the vertical axis.
[0066] The strength of the sample solution was tested and the lanthanum content was found on the calibration curve. The test results are shown in Table 3.
[0067] Table 3
[0068]
[0069] In Comparative Example 2, lanthanum was dissolved in a low-temperature electric furnace with hydrogen peroxide, and then heated in an ammonia water bath to precipitate lanthanum. The lanthanum in the tungsten alloy sample was not completely converted into lanthanum hydroxide precipitate, resulting in a low test result, and the accuracy was worse than that of Example 1, and the stability was also poor.
[0070] Comparative Example 3
[0071] The tungsten alloy sample to be tested was crushed, 0.15g was weighed and placed in a polytetrafluoroethylene beaker, moistened with water, 10mL of nitric acid and 2mL of hydrofluoric acid were added to completely dissolve the tungsten alloy sample at 70°C, cooled, transferred to a 100mL volumetric flask, and diluted to the scale with water. The sample solution to be tested was obtained, and a blank test was performed together with the sample;
[0072] Drawing of standard working curve: Pipette 0.00mL, 0.50mL, 1.0mL, 2.0mL, 5.0mL, 10.0mL of lanthanum standard solution (100μg / mL) into a 100mL volumetric flask, add 5mL of nitric acid, dilute to scale with water, and mix well. Introduce the series of standard solutions into the inductively coupled plasma atomic emission spectrometer, measure the intensity of lanthanum in the series of standard solutions at the selected wavelength, and draw the calibration curve with mass concentration as the horizontal axis and intensity as the vertical axis.
[0073] The strength of the sample solution was tested and the lanthanum content was found on the calibration curve. The test results are shown in Table 4.
[0074] Table 4
[0075]
[0076] Comparative Example 3: When the tungsten alloy sample to be tested is crushed, some impurity elements will be brought in. When the sample is dissolved by nitric acid-hydrofluoric acid, more reagents and time are needed when the impurity content is high, and there is also a certain interference with the elements to be tested. In addition, hydrofluoric acid has a corrosive effect on glass, and the inductively coupled plasma atomic emission spectrometer must be equipped with a hydrofluoric acid-resistant injection system, which increases the cost and affects its detection precision and accuracy to a certain extent.
[0077] Comparative Example 4
[0078] The difference from Example 1 is that the tungsten alloy sample to be tested is oxidized at 850° C. for 6 hours in a muffle furnace without introducing compressed air.
[0079] The strength of the sample solution was tested and the lanthanum content was found on the calibration curve. The test results are shown in Table 5.
[0080] Table 5
[0081]
[0082] In comparative example 4, after 6 hours of oxidation without compressed air, it was found that the sample was still not completely oxidized, which affected the subsequent test results.
[0083] Comparative Example 5
[0084] The difference from Example 1 is that the operation of taking out the tungsten alloy sample every hour to separate the oxide powder is not performed.
[0085] The strength of the sample solution was tested and the lanthanum content was found on the calibration curve. The test results are shown in Table 6.
[0086] Table 6
[0087]
[0088] In Comparative Example 5, the operation of taking out the tungsten alloy sample every 1 hour to separate the oxide powder was not performed. Tungsten oxide adhered to the surface of the tungsten alloy, and the sample was difficult to oxidize, which affected the subsequent test results.
[0089] The present invention adopts an inductively coupled plasma atomic emission spectrometer to determine the lanthanum element, and has the advantages of high precision, simple operation, less interference, low detection limit, etc. The present invention can avoid the pollution caused by sample pretreatment by subjecting the sample to be tested to high temperature oxidation, the oxidized sample is dissolved by hydrogen peroxide, lanthanum is precipitated with magnesium as a carrier in an alkaline medium of triethanolamine solution, tungsten matrix is effectively removed by filtration and separation, the precipitate is dissolved with nitric acid and perchloric acid, and in a dilute nitric acid medium, it is directly excited with an argon plasma light source, so as to achieve the purpose of eliminating background and spectral line interference, improve accuracy, and can well meet the determination requirements of the rare earth element La in tungsten alloy.
[0090] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for determining the La content in tungsten alloy, characterized in that: The steps include: S1. The tungsten alloy sample to be tested is oxidized by passing compressed air into a muffle furnace to obtain oxide powder; during the oxidation process, the sample is taken out every 1 to 2 hours; S2. The oxide powder is transferred into a beaker, and hydrogen peroxide is added and then placed in a water bath for dissolution. After the yellow solid disappears, the solution is taken out from the water bath to obtain a solution, and then ammonia water is added after cooling to room temperature to prepare a clear solution; S3, adding triethanolamine solution to the clarified solution, precipitating lanthanum with magnesium salt as a carrier, filtering and separating with filter paper, and discarding the filtrate; S4. Place the precipitate together with the filter paper in the original beaker, add a mixed solution of nitric acid and perchloric acid, place on a heating plate and heat to dissolve, to prepare a sample solution to be tested; S5. Use an inductively coupled plasma atomic emission spectrometer to draw a tungsten alloy calibration curve, and measure the La intensity of the sample solution to be tested. The La content is obtained through the calibration curve to achieve the determination of the La element content in the tungsten alloy.
2. The method for determining the La content in tungsten alloy according to claim 1, wherein: In the step S1, the oxidation temperature is 750-850° C., the oxidation time is 1-6 hours, and the compressed air flow rate is 1.5-3 L / min.
3. The method for determining the La content in tungsten alloy according to claim 1, wherein: In step S1, the sample taken out during the oxidation process is placed in a dryer for cooling, the surface of the sample is cleaned, the oxide is separated from the tungsten alloy sample, and then the tungsten alloy sample is placed in a muffle furnace for oxidation, and the operation is repeated until the tungsten alloy sample is completely oxidized.
4. The method for determining the La content in tungsten alloy according to claim 1, wherein: In step S2, the water bath temperature is 60-80°C.
5. The method for determining the La content in tungsten alloy according to claim 1, wherein: In the step S2, the solid-liquid ratio of the oxide powder to hydrogen peroxide is (0.10-0.20) g: (10-30) mL.
6. The method for determining the La content in tungsten alloy according to claim 1, wherein: In step S2, the concentration of ammonia water is 25-28 wt %, and the volume ratio of ammonia water to the dissolving liquid is (1-3): (15-30).
7. The method for determining the La content in tungsten alloy according to claim 1, wherein: In step S3, the concentration of the triethanolamine solution is 1-5 wt %, and the volume ratio of the clear solution to the triethanolamine solution is (1-30):(1-6).
8. The method for determining the La content in tungsten alloy according to claim 1, wherein: In step S3, the magnesium salt is added in the form of a solution, the concentration of the magnesium salt solution is 1-5 wt %, and the volume ratio of the clear solution to the magnesium salt solution is (1-30):(1-3).
9. The method for determining the La content in tungsten alloy according to claim 1, wherein: In the step S4, the dissolving temperature is 100-150°C.
10. The method for determining the La content in tungsten alloy according to claim 1, wherein: In step S4, the volume ratio of nitric acid to perchloric acid in the mixed solution of nitric acid and perchloric acid is (1-10):(1-3), and the concentration of the mixed solution of nitric acid and perchloric acid is 30-50wt%.
Citation Information
Patent Citations
Method for analyzing and detecting cadmium impurity element in tungsten or tungsten compound
CN102854179A
Method for detecting content of rare earth elements in tungsten and molybdenum materials
CN116818879A